Species-Specific Trait Responses of Three Tropical Seagrasses to Multiple Stressors: The Case of Increasing Temperature and Nutrient Enrichment - Viana, Inés G.; Moreira-Saporiti, Agustín; Teichberg, Mirta (Frontiers in Plant Science, 2020)
Seagrass meadows are declining globally. The decrease of seagrass area is influenced by the simultaneous occurrence of many factors at the local and global scale, including nutrient enrichment and climate change. This study aims to find out how increasing temperature and nutrient enrichment affect the morphological, biochemical and physiological responses of three coexisting tropical species, Thalassia hemprichii, Cymodocea serrulata and Halophila stipulacea. To achieve these aims, a one-month experiment under laboratory conditions combining two temperature (maximum ambient temperature and current average temperature) and two nutrient (high and low N and P concentrations) treatments was conducted. The results showed that the seagrasses were differentially affected by all treatments depending on their life-history strategies. Under higher temperature treatments, C. serrulata showed photo-acclimation strategies, while T. hemprichii showed decreased photo-physiological performance. C. serrulata also showed nutrient loss in below-ground (BG) tissues, while H. stipulacea was unaffected in terms of morphological and biochemical traits. In contrast, T. hemprichii was resistant to nutrient over-enrichment, showing enhanced nutrient content and physiological changes, but C. serrulata suffered BG nutrient loss. The lack of response of H. stipulacea to nutrient enrichment or high temperature suggests that this seagrass is a tolerant species that may have a dormancy state with lower photosynthetic performance and smaller-size individuals. Interaction between both factors was limited and generally showed antagonistic effects only on morphological and biochemical traits, but not on physiological traits. These results highlight the different effects and strategies co-inhabiting seagrasses have in response to environmental changes, showing winners and losers of a climate change scenario that may eventually cause biodiversity loss. Trait responses to these stressors could potentially make the seagrasses weaker to cope with following events, due to BG biomass or nutrient loss. This is of importance as biodiversity loss in tropical seagrass ecosystems could change the overall effectiveness of ecosystem functions and services provided by the seagrass meadows.